Testes clínicos adaptados para avaliação da força muscular em idosos com doença de Alzheimer: um estudo de revisão sistemática, confiabilidade e validade - Oliveira, Marcos Paulo Braz de (Universidade Federal de São Carlos, 2023)
The overarching aim of this Doctoral Thesis was to determine the measurement properties of the adapted Five-Times Sit-to-Stand (5STS), 30-Second Sit-to-Stand (30STS) and Calf-Rise Senior (CRS) tests to assess lower limb muscle strength in older adults with Alzheimer’s disease (AD). Standardized verbal commands were provided throughout the test execution with the purpose of assisting participants with test initiation and completion. Verbal commands included “stand up” and “sit down” (for 5STS and 30STS) and “stand on your tip toes” and “now you can get down” (for CRS). Three main Studies lead the investigation for this Doctoral Thesis. Study I aimed to systematically investigate the literature to assess test assessments reliability in respects to physical function in older adults with dementia. This systematic investigation focused on muscle strength, potential test assessment adaptations, and older adults with AD. Study II investigated the reliability of isokinetic dynamometry for assessing knee and ankle muscle strength (i.e., joint torque) in older adults with AD. Study III determined the reliability and concurrent validity of the 5STS, 30STS and CRS adapted tests to assess lower limb muscle strength in older adults with AD. Study I identified 15 reliability studies with a total of 560 participants (i.e., older adults with dementia), and 19 clinical tests to assess physical function. Three of these tests specifically addressed lower limb muscle strength (i.e., 5STS, 30STS and Hand-Held Dynamometer) and were shown to be reliable for physical function assessment in older adults with dementia. Verbal commands and/or physical assistant was needed for the test execution however, verbal command standardization was not observed. In Study II, a total 42 older adults with AD were evaluated with 22 participants being in the mild stage of disease progression and 20 in the moderate-stage. Additionally, 20 older adults with preserved cognition were included as controlled comparison. Study II identified that isokinetic measures (i.e., peak torque, average peak torque, and total work) are reliable for assessing knee and ankle muscle strength (i.e., joint torque) in older adults with AD in the mild and moderate stages. In Study III, a total 42 older adults with AD were evaluated (22 participants in the mild stage of disease progression and 20 in the moderate-stage). Study III findings indicated that the adapted 5STS, 30STS and CRS tests are reliable for assessing lower limb muscle strength and are correlated with measure of lower limb maximal muscle strength and power in older adults with AD.
Adapted clinical tests for the assessment muscle strength in older adults with Alzheimer's disease: a systematic review, reliability and validity study
Keywords: Envelhecimento; Demência; Doença de Alzheimer; Saúde do idoso; Força muscular; Reprodutibilidade dos testes; Classificação internacional de funcionalidade, incapacidade e saúde; Aging; Dementia; Alzheimer disease; Health of the elderly; Muscle strength; Reproduticibility of results; International classification of functioning, disability and health; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL